Assessing the feasibility of assisted migration of corals in the Red Sea - Barreto, Marcelle Muniz; Schmidt-Roach, Sebastian; Zhong, Huawen; Aranda, Manuel (Frontiers in Marine Science, 2023)
Climate change, and in particular the unprecedented rapid global warming, presents a major threat to corals, with warming rates potentially exceeding the adaptive capacities of most coral species. Assisted gene flow, the human facilitated introduction of temperature resilience alleles from warmer to threatened colder populations via the movement of individuals (assisted migration) or their gametes (selective breeding), has been suggested as a tool to transfer thermal adaptations among populations. Due to its strong latitudinal temperature gradient and extreme temperature conditions, the Red Sea constitutes an ideal location to investigate the potential of this strategy. Here, we relocated Porites lobata colonies from three reefs along the Saudi Arabian Red Sea with different mean sea surface temperature summer maxima (ranging from 30.9 °C in Duba, 32.5 °C in Thuwal, to 33.8 °C in Jazan) to a common garden experiment in the intermediate central location. Five colonies from each location were fragmented and deployed in situ in early summer of 2018 to investigate physiological differences in bleaching, survival, and growth. Results showed significantly higher bleaching in fragments from Duba, followed by 65% mortality. Even though no bleaching was observed in fragments from Jazan, mortality rates of around 20% indicated that other environmental parameters besides temperature might influence coral health and survival. These results suggest that assisted gene flow via translocation alone may be restricted in its success due to a lack of local adaptations to environmental conditions other than temperature. However, strategies like inter-populational breeding may overcome these limitations as they might allow producing offspring with both increased thermal tolerance and local adaptations.